Bacterial Biofilm Communities and Coral Larvae Settlement at Different Levels of Anthropogenic Impact in the Spermonde Archipelago, Indonesia - Kegler, Pia; Kegler, Hauke F.; Gärdes, Astrid; Ferse, Sebastian C. A.; Lukman, Muhammad; Alfiansah, Yustian R.; Hassenrück, Christiane; Kunzmann, Andreas (Frontiers in Marine Science, 2017)
Populations on small islands surrounded by coral reefs often heavily depend on the services provided by these reefs. The health and recovery of reefs are strongly influenced by recruitment of coral larvae. Their settlement relies on cues such as those emitted from bacterial communities forming biofilms on reef surfaces. Environmental conditions can change these bacterial community compositions (BCC) and may in turn affect settlement of coral larvae. At three small inhabited islands in the Spermonde Archipelago, Indonesia, with different distance from the mainland, BCC and coral recruitment were investigated on artificial ceramic tiles after 2-8 weeks exposure time and on natural reef substrate. Water parameters showed a clear separation between inshore and near-shore/mid-shelf sites, with distinct benthic communities at all three sites. No coral recruitment was observed at the inshore site with highest natural and anthropogenic stressors. At the other two sites coral recruitment occurred on natural surfaces (recruits per 100 cm2: 0.73 ± 1.75 near-shore, 0.90 ± 1.97 mid-shelf), but there was no significant difference between the two sites. On artificial substrates coral recruitment differed between these two sites, with tile orientation and with exposure time of the tiles in the reef. The most abundant bacteria on both substrates were Gammaproteobacteria, Alphaproteobacteria and Cyanobacteria. BCC was strongly correlated with water quality and significant differences in BCC between the inshore site and near-shore/mid-shelf were found. On artificial substrates there was a significant difference in BCC also with exposure time in the reef. Our study highlights the value of taking both BCC and coral recruitment into account, in addition to the environmental conditions, when considering the recovery potential of coral reefs.